2014
DOI: 10.3917/spub.144.0541
|View full text |Cite
|
Sign up to set email alerts
|

Connaissances, attitudes et pratiques de la contraception d'urgence chez les étudiantes à l'Université de Parakou (Bénin)

Abstract: Students were familiar with and had easy access to the method. However, repeated use of this method highlights the need for better information of these students concerning classical methods of contraception. An awareness campaign should be conducted on the campus in order to reduce the currently high rate of non-medical clandestine abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…11 In surveys, women who had been unfamiliar with emergency contraception often responded to information and questions about the method with a mix of interest and caution regarding its long-term side effects (some expressed concern about sterility) and routine use. [13][14][15] Research on advance or over-the-counter provision of emergency contraceptive pills has yielded a strong consensus that this service delivery strategy is safe, but conflicting findings on its impact on preventing unintended pregnancies among either adults or adolescents. 16 Similarly, research on whether advance provision of emergency contraceptive pills will increase repeat or routine use of the method has been inconclusive.…”
Section: Conclusion: Emergency Contraceptive Pills Have the Potentiamentioning
confidence: 99%
See 1 more Smart Citation
“…11 In surveys, women who had been unfamiliar with emergency contraception often responded to information and questions about the method with a mix of interest and caution regarding its long-term side effects (some expressed concern about sterility) and routine use. [13][14][15] Research on advance or over-the-counter provision of emergency contraceptive pills has yielded a strong consensus that this service delivery strategy is safe, but conflicting findings on its impact on preventing unintended pregnancies among either adults or adolescents. 16 Similarly, research on whether advance provision of emergency contraceptive pills will increase repeat or routine use of the method has been inconclusive.…”
Section: Conclusion: Emergency Contraceptive Pills Have the Potentiamentioning
confidence: 99%
“…11 A finding common to all studies of emergency contraceptives in Sub-Saharan Africa is that knowledge of the method's 120-hour maximum time frame and its mechanisms of action are extremely limited, even among groups in which method awareness is higher than in the general population. 14,19,20 In addition, it is unclear whether the recourse to noncontraceptive drugs and folk remedies documented in the 1990s as postcoital contraceptive regimens 21 is still a common occurrence.…”
Section: Conclusion: Emergency Contraceptive Pills Have the Potentiamentioning
confidence: 99%
“…However, the practice of modern contraceptive methods in general has a difficult time winning over women in Africa. 9 In several African countries, healthcare providers are limiting information on EC, fearing abuse or increased risk of sexual behavior or neglect of traditional contraceptive methods. 9 However, studies that have shown the opposite point out that the use of the EC must be ad hoc without hindering women's contraceptive habit.…”
Section: Discussionmentioning
confidence: 99%
“…EC is indicated to prevent pregnancy after unprotected or inadequately protected sex. 9 A study of female students at the University of Parakou (Benin) showed that only 51% of respondents had ever heard of EC. 9 Another study of female students in Botswana reported that overall knowledge of EC was 95% and only 22% had used it at least once.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation